Neurobiological Differences Between Aggression and Agitation in Persons with DementiaAffiliation - Volicer Ladislav (Journal of Neurological Research And Therapy, 2019)
Background Controversy exists about definition of agitation and especially about inclusion of aggression as a part of agitation in people with dementia. Methods Papers describing neurobiological indices related to behavioral symptoms of dementia were reviewed. Papers comparing indices in persons exhibiting aggression and persons exhibiting agitation were selected for this review. Results The survey found seven papers which compared neuroanatomical indices and three papers which compared neurochemical indices. The neuroanatomical indices differentiating agitation and aggression included changes in brain perfusion, sizes of brain areas, distribution of neurofibrillary tangles, and white matter changes. The neurochemical indices differentiating agitation and aggression included relationships with neurotransmitter variables and the cell count in the locus coeruleus. Conclusion Despite the small number of papers and some methodological problems, the presented information clearly indicates that aggression and agitation are two distinct unrelated syndromes in persons with dementia.
Keywords: dementia